The nature and impact of antidepressant withdrawal symptoms and proposal of the Discriminatory Antidepressant Withdrawal Symptoms Scale (DAWSS) - Joanna Moncrieff; John Read; Mark Abie Horowitz (Journal of Affective Disorders Reports, 2024)
Background: We sought to understand more about the nature and possible consequences of antidepressant withdrawal. Methods: We surveyed members of 20 peer-led, online groups, assessing 31 commonly reported antidepressant withdrawal symptoms. Results: There were 1148 respondents, who were mostly white, female and educated. For 40 % of respondents, withdrawal symptoms had lasted more than 2 years and 80 % were moderately or severely impacted by them. One in four were unable to stop their antidepressant. Reported consequences of withdrawal included impaired work function (56 %), losing jobs (20 %), taking sick leave (27 %), and relationship breakdown (25 %). Both emotional and physical symptoms newly occurred or increased in severity following antidepressant withdrawal compared to before starting antidepressants. There was no difference in the nature of symptoms, severity or duration between people with physical or mental health diagnoses. We have proposed a potential Discriminatory Antidepressant Withdrawal Symptoms Scale (DAWSS), comprising the 15 symptoms most specific to withdrawal (including electric shock sensations, dizziness, akathisia or restlessness, vertigo, and vomiting), which requires further validation. Limitations: The sample was derived from peer support groups and is not representative of everyone who undergoes antidepressant withdrawal. The cross-sectional design precludes establishing causal relationships between variables. Conclusions: Our findings suggest there is a distinctive antidepressant withdrawal syndrome characterised by a range of emotional and physical symptoms, which can be severe, prolonged and have profound impact. The DAWSS may be helpful in distinguishing withdrawal from underlying conditions. Health services need to provide evidence-based clinical advice and support to people on long-term antidepressants.